Identifikasi Kesesuaian Genotipe Kedelai untuk Tumpang Sari dengan Ubi Kayu - Titik Sundari; Siti Mutmaidah (Jurnal Ilmu Pertanian Indonesia, 2018)
Intercropping is a modification of crop arrangements that can provide significant improvements in yields, with minimal labor investment. Increased productivity in soybean intercropping with cassava can be achieved through the use of suitable soybean genotypes for intercropping, as each genotype shows different responses to intercropping. The research aimed to identify the suitability of soybean genotypes for intercropping with cassava based on yield and land productivity assessed by the land equivalent ratio (LER). The research in 2016 was conducted at Kendalpayak Station Research, Malang, using a split plot design, repeated three times. The main plot is fifty-five soybean genotypes (50 promising lines and five control varieties, namely: Argopuro, Panderman, Dena 1, Dena 2, and Grobogan), and the sub plot is cropping systems (monoculture and intercropping). The results showed that intercropping of soybean with cassava caused soybean plants to experience shade stress, with shade rate of 62-90, 43-77, and 0-40% respectively for first, second and third-row positions. There are six soybean genotypes suitable for intercropping with cassava, Grob/Argom313-2, Grob/Pander395-3, Grob/Pander405-3, Grob/Pander428-1, Grob/Pander429-2, and Grob/IAC439-2, with an LER value of ≥1.8 which is a 10% selection limit to LER. Four combinations of them (Grob/Pander395-3, Grob/Pander405-3, Grob/Pander428-1, and Grob IAC439-2) provide an increase in cassava yields between 7.7-19.7% and reduction of soybean yields between 21.4-38.5%. While the two combinations other (Grob/Argom313-2 and Grob/Pander429-2) provide a reduction of cassava yields by 1.4 and 8.5% and reduction of soybean yield by 23.5 and 7.1%.